Biaxial stretchable liquid crystal light scattering display based on uniform energy dissipation in non-oriented assembly of gel networks. Issue 38 (16th September 2020) - Du, Qinqing; Shan, Tianyu; Du, Junnan; He, Huiwen; Ma, Meng; Shi, Yanqin; Chen, Si; Wang, Xu
Abstract : Different from the traditional uniaxial stretchable displays, biaxial stretchable devices are herein reported based on a dynamic supramolecular liquid crystal gel network that showed good innovation in a new dimension of the original stretch to obtain the "true stretchable display". Abstract : Different from the traditional uniaxial stretchable displays, biaxial stretchable devices are herein reported based on a dynamic supramolecular liquid crystal gel network that showed good innovation in a new dimension of the original stretch to obtain the "true stretchable display". Such biaxial stretchable displays can depict information and images clearly under biaxial forces, which are investigated for breaking the dimensional limitation of traditional uniaxial stretch displays and provide a new perspective for stretchable displays. Unlike the commonly used polymer-based display layer, which was not able to achieve equal and uniform bearing of external forces in perpendicular directions, this unique supramolecular network topography favours the dissipation of tensile forces in two-dimensions through the network structure based on the unique non-oriented assembly. This unique biaxial stretchable optical display paves the way for future stretchable devices.